2021
DOI: 10.1186/s12935-021-02095-4
|View full text |Cite
|
Sign up to set email alerts
|

MINDY1 promotes bladder cancer progression by stabilizing YAP

Abstract: Background Bladder cancer is one of the most commonly diagnosed urological malignant tumor. The Hippo tumor suppressor pathway is highly conserved in mammals and plays an important role in carcinogenesis. YAP is one of major key effectors of the Hippo pathway. However, the mechanism supporting abnormal YAP expression in bladder cancer remains to be characterized. Methods Western blot was used to measure the expression of MINDY1 and YAP, while the Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…50 In BE and EAC, MINDY1 was identified in a set of 90 genes significantly predicting disease progression by distinguishing EAC progressors from patients with non-dysplastic BE. 51 Moreover, MINDY-1 was found to promote bladder cancer progression by stabilizing YAP, 52 a key tumorigenesis pathway member that can also be induced by conjugated bile acids in EAC. 53 In our analysis, increased usage of the MINDY1 transcript that lacks deubiquitinase (DUB) domains and a decreased usage of the MINDY1 transcript that contains five DUB domains are observed, potentially suggesting impaired MINDY-1 function during EAC progression.…”
Section: Discussionmentioning
confidence: 99%
“…50 In BE and EAC, MINDY1 was identified in a set of 90 genes significantly predicting disease progression by distinguishing EAC progressors from patients with non-dysplastic BE. 51 Moreover, MINDY-1 was found to promote bladder cancer progression by stabilizing YAP, 52 a key tumorigenesis pathway member that can also be induced by conjugated bile acids in EAC. 53 In our analysis, increased usage of the MINDY1 transcript that lacks deubiquitinase (DUB) domains and a decreased usage of the MINDY1 transcript that contains five DUB domains are observed, potentially suggesting impaired MINDY-1 function during EAC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Co-immunoprecipitation (Co-IP) was performed as described in a previous study [ 23 ]. The cells were lysed in lysis buffer (Aspen Biological) and approximately 200 μg of total cellular proteins were incubated overnight with target antibody at 4 °C followed by the addition of 20 μL of protein A agarose beads (#1614813, BIO-RAD).…”
Section: Methodsmentioning
confidence: 99%
“…While there is limited work examining the role of YAP in BCa recurrence, a study by Ghasemi et al reported higher YAP expression in recurrent BCa [ 110 ]. There is additional work looking more broadly at agents that modulate BCa progression through YAP [ 111 , 112 ] and at molecules, including miRNAs, that affect BCa development through YAP [ 113 , 114 ]. YAP is also involved in BCa chemoresistance, with studies examining the naturally-derived ailanthone as an inhibitor of proliferation and migration in cisplatin-resistant BCa cells through YAP and Nrf2 repression [ 115 , 116 ].…”
Section: Hippo Signalingmentioning
confidence: 99%